Metric-Resolution 2D River Modeling at the Macroscale: Computational Methods and Applications in a Braided River - Schubert, Jochen E.; Monsen, Wade W.; Sanders, Brett F. (Frontiers in Earth Science, 2015)
Metric resolution digital terrain models (DTMs) of rivers now make it possible for multi-dimensional fluid mechanics models to be applied to characterize flow at fine scales that are relevant to studies of river hydraulic geometry (HG) and ecological habitat, or microscales. These developments are important for managing rivers because of the potential to better understand system dynamics, anthropogenic impacts, and the consequences of proposed interventions. However, the data volumes and computational demands of microscale river modeling have largely constrained applications to small multiples of the channel width, or the mesoscale. This report presents computational methods to extend a microscale river model beyond the mesoscale to the macroscale, defined as large multiples of the channel width. A method of automated unstructured grid generation is presented that automatically clusters fine resolution cells in areas of curvature (e.g., channel banks), and places relatively coarse cells in areas lacking topographic variability. This overcomes the need to manually generate breaklines to constrain the grid, which is painstaking at the mesoscale and virtually impossible at the macroscale. The method is applied to a braided river (BR) and shown to yield an efficient fine resolution model. The sensitivity of model output to grid design and resistance parameters is also examined based on analysis of hydrology, HG, and river hydraulic habitats and the findings reiterate the importance of model calibration and validation.